2013
DOI: 10.1080/10556788.2013.823544
|View full text |Cite
|
Sign up to set email alerts
|

Strict linear prices in non-convex European day-ahead electricity markets

Abstract: The European power grid can be divided into several market areas where the price of electricity is determined in a day-ahead auction. Market participants can provide continuous hourly bid curves and combinatorial bids with associated quantities given the prices. The goal of our auction is to maximize the economic surplus of all participants subject to quantity constraints and price constraints. The price constraints ensure that no one incurs a loss. Only traders who submitted a combinatorial bid might miss a n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 13 publications
0
27
0
4
Order By: Relevance
“…EMCC passed on its duty to its successor NorthWestern Europe (NWE) price coupling system (including countries Denmark, Finland, Norway, Sweden, Great Britain, Belgium, France, Germany, Luxemburg and the Netherlands) in February 2014. Finally, PCR project combined NWE and South-Western Europe (SWE) regions by using EUPHEMIA (Pan-European Hybrid Electricity Market Integration Algorithm) in May 2014 [25,24,9].…”
Section: Liberalization Of the Dutch Electricity Marketmentioning
confidence: 99%
“…EMCC passed on its duty to its successor NorthWestern Europe (NWE) price coupling system (including countries Denmark, Finland, Norway, Sweden, Great Britain, Belgium, France, Germany, Luxemburg and the Netherlands) in February 2014. Finally, PCR project combined NWE and South-Western Europe (SWE) regions by using EUPHEMIA (Pan-European Hybrid Electricity Market Integration Algorithm) in May 2014 [25,24,9].…”
Section: Liberalization Of the Dutch Electricity Marketmentioning
confidence: 99%
“…The startup costs of power plants and industrial electricity consumers create complementarities across consecutive operating hours and create motivation for bidders to place bids for a consecutive set of hours to avoid multiple setups (Wolfram 1998, Hortaçsu and Puller 2008, Reguant 2014. Hence, liberalized electricity markets allow some form of complementary bidding, and thus, combinatorial auctions are designed to determine electricity prices (Meeus et al 2009, Martin et al 2014, Derinkuyu 2015. Unlike the combinatorial auctions discussed previously, in which the winner receives its bid price, in electricity markets, a single MCP is used to pay market participants.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The authors also ex plore the impact of block orders on the complex ity of the problem and report how the solution time changes with the density of block orders. Martin et al (2014 ) ex tend Meeus et al (2009) by (1) allowing for interpolation of price and quantity bids and (2) considering mul tiple pricing regions with transmission capacity limits among them. This leads to a more complex MINLP formulation for the day-ahead price optimization.…”
Section: Academic Research On Dam Optimizationmentioning
confidence: 99%
“…Derinkuyu (2014a) introduces an innovative approach to the prob lem by minimizing prices while representing social welfare in the constraint set. His approach also results in an MIP, which is consid erably simpler than Martin et al (2014). Derinkuyu (2014a) showed that problem size reduction techniques can be effective.…”
Section: Academic Research On Dam Optimizationmentioning
confidence: 99%